2008
DOI: 10.1007/s10787-008-8016-9
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative activities and the total phenolic contents of tonic Chinese Medicinal Herbs

Abstract: Chinese medicated diet is an everyday practice in China. In this study, 16 commonly used soup making tonic Chinese medicinal herbs were selected for antioxidative capacities by 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging activity and ferric reducing antioxidant power (FRAP), and the total phenolic contents of these herbal extracts were measured by the Folin-Ciocalteu method. It confirmed that drinking tonic soups could supplement total antioxidants intake. Amongst the tested herbal extracts, extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(48 citation statements)
references
References 30 publications
3
43
1
1
Order By: Relevance
“…Five normal and 35 STZ-induced diabetic rats were assigned to eight groups of five rats each and treated consecutively for 14 FBG and body weight of the rats were measure at outset of the experiment (baseline fasting blood glucose), day 7 and at the end of study (day 14).…”
Section: Fourteen Days Consecutive Oral Administration Of Extracts Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…Five normal and 35 STZ-induced diabetic rats were assigned to eight groups of five rats each and treated consecutively for 14 FBG and body weight of the rats were measure at outset of the experiment (baseline fasting blood glucose), day 7 and at the end of study (day 14).…”
Section: Fourteen Days Consecutive Oral Administration Of Extracts Ofmentioning
confidence: 99%
“…A series of standard gallic acid solutions μg/mL) were prepared and absorbance measured at same wavelength and data used to plot the calibration curve. The total phenolic content was calculated as μg/mL of gallic acid equivalent of extracts [7] . All samples were analyzed in triplicates.…”
Section: Determination Of Total Phenolicsmentioning
confidence: 99%
“…Fructus Amomi is one of the herbal medicines which has an effect on the clinical therapy of abdominal pain, vomiting and dysentery mainly attributed to its essential oil. [26][27][28] In this study, a posttarget method was applied for the determination of volatile compounds in Fructus Amomi based on gas chromatography quadrupole time-of-flight mass spectrometry (GC-Q-ToF-MS), with more volatile compounds being identified compared with conventional methods. Meantime, the accurate mass of fragment ions acquired by GC-Q-ToF-MS showed greatly helped in the confirmation of structure identification.…”
Section: European Journal Of Mass Spectrometrymentioning
confidence: 99%
“…Commonly, five main classes of components, such as volatile oils, saponins, flavonoid glycosides, organic acids and inorganic components are contained in A. xanthoides. Several studies have indicated that A. xanthoides has antiinflammatory, antiallergic, antidiabetic and antioxidative effects in both human subjects and animal models (Guo et al, 2008;Kim & Shin, 2005;Park & Park, 2001;Wu et al, 2004). In addition, A. xanthoides is also one component of the herbal hepatotherapeutic formula Chungan extract, the efficacy of which had been demonstrated both in clinical trials and in several animal models (Cho et al, 2001;Shin et al, 2006;Wang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%